Psychological well-being and everyday activities in rural and urban teachers in North of Santander during the COVID-19 pandemic (2022)
This research review shows how isolation due to the COVID-19 pandemic has affected daily activities such as quality of sleep, physical activity, and work life. This review exercise is developed to provide information that will help different professionals to point out the psychological impact and possible changes presented in the daily activities of people during confinement. Sleep hygiene and quality of sleep were affected due to factors such as age - young, sex - female, history of mental illness, insomnia, anxiety, depression, psychological distress, low back pain, and stress. With regard to physical activity during preventive isolation, it was found that there was a lack of physical exercise, weight gain, increased sedentary life, decreased outdoor activities, increased consumption of cigarettes, alcohol, and the use of electronic devices, as well as increased intake of ultra-processed foods. As for the work activity during COVID-19, there were difficulties in the adaptation and qualification to the management of Tics, and work overload, in addition, it is observed that the predominant gender is female, and there is psychological and mental affectation and emotional exhaustion.